2017
DOI: 10.17219/acem/62835
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous scaffolds supplemented with hyaluronic acid and chondroitin sulfate used for wound fibroblast and embryonic nerve cell culture

Abstract: Background. Tissue engineering is a strategy aimed at improving the regeneration of injured tissues.Objectives. The aim of the present study was to determine whether a tri-copolymer composed of crosslinked collagen, chondroitin sulfate and hyaluronic acid (Col + CS + HA) provides a better environment for fibroblast and embryonic nerve cell culture than a collagenous scaffold (Col).Material and methods. The porosity of each of the matrices was characterized with a scanning electron microscope. Fibroblasts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
(47 reference statements)
1
6
0
2
Order By: Relevance
“…Flow cytometry studies have found that the embryonic nerve cells seeded within the scaffolds contained cells differentiating into neurons (MAP2-positive cells) (7,8); these are able to replace the damaged nervous tissue at the site of trauma, and are hence, crucial for tissue reconstruction. Scaffolds populated with embryonic nerve cells are also believed to be a source of cytokines that may accelerate the regeneration process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Flow cytometry studies have found that the embryonic nerve cells seeded within the scaffolds contained cells differentiating into neurons (MAP2-positive cells) (7,8); these are able to replace the damaged nervous tissue at the site of trauma, and are hence, crucial for tissue reconstruction. Scaffolds populated with embryonic nerve cells are also believed to be a source of cytokines that may accelerate the regeneration process.…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic rats were euthanized by decapitation before brain isolation. The embryos at day 17 of gestation were isolated from the uterus of the pregnant female rat in sterile cold PBS (7,8). Once removed from the embryos, the brains were rinsed with PBS, and the meninges and blood vessels were excised.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Collagen is a very good vehicle for drug and cell delivery ( Dalamagkas et al, 2016 ) and it is possible to modify its physical features along different parts of the same conduit ( Aigner et al, 2020 ). The different binding domains on it give the possibility to create topographical cues that guide the axon regrowth ( Stang et al, 2005a , b ) facilitating cell adhesion, survival and migration ( Alberti et al, 2014 ; Sulong et al, 2014 ; Drobnik et al, 2017a , b ). Many researchers have shown that collagen has biological properties superior to other materials available in the market for nerve scaffold fabrication and it is also effective over a nerve gap distance of at least 15 mm ( Archibald et al, 1991 ).…”
Section: Natural-based Biomaterialsmentioning
confidence: 99%